The canonical Wnt pathway in osteoporosis: a scoping review of key compounds and proteins modulating Wnt-induced osteogenesis - Elahmer, Nyruz; Mohamed, Norazlina; Wong, Sok Kuan; Jamil, Nur Khadijah Muhamad; Mohamed, Isa Naina; Mokhtar, Sabarul Afian; Muhammad, Norliza (Frontiers in Pharmacology, 2025)
PurposeThe canonical Wnt pathway—a key regulator of bone formation and remodeling—has emerged as a promising target for osteoporosis therapy. This scoping review aims to map the key compounds and proteins modulating Wnt-induced osteogenesis, providing a comprehensive overview of the current literature and identifying research gaps.MethodsA systematic search was conducted in Ovid and PubMed for studies published between June 2017 and August 2025. Two independent reviewers screened titles, abstracts, and full texts. Data were extracted and synthesised narratively.ResultsAmong 108 articles identified, 22 met the inclusion criteria. External compounds such as LG-HMF, cerium oxide nanoparticles, 6% Sr-MSNs, and platelet-rich plasma (PRP) were found to stimulate Wnt signaling, promoting osteogenesis and inhibiting osteoclastogenesis via diverse mechanisms. Molecular agents including β-sitosterol and fluoxetine also modulated the pathway, suggesting novel therapeutic opportunities. Internal regulators such as LINC01119, QKI, and PITX1 inhibited Wnt activity and were associated with bone loss, while GNAS, GCN5, and Ca(v)1.2 activated the pathway, enhancing bone health. The review highlights intricate crosstalk between canonical and Notch pathways and non-canonical Wnt pathways in bone remodeling. Clinical and epidemiological studies further confirmed the relevance of Wnt signaling by linking specific genetic and protein markers to bone mineral density and fracture risk.ConclusionThis scoping review highlights the dual role of Wnt pathway modulators—stimulators enhance bone formation, while inhibitors contribute to osteoporosis—emphasizing its potential in guiding targeted therapies and identifying genetic markers for personalized osteoporosis treatment.